Prevalence of naturally occurring antisperm antibodies (ASA) in blood serum and seminal plasma, and their relationship with cryopreserved semen quality and fertility of buffalo bulls - SINGH, A K; CHEEMA, RANJNA S (The Indian Journal of Animal Sciences, 2018)
The present study was undertaken to determine the levels of antisperm antibodies (ASA), sperm-bound immunoglobulins A and G (IgA and IgG) in blood serum and seminal plasma of breeding buffalo bulls, and establish their relationship with quality and fertility of cryopreserved semen. Frozen semen (50 straws/bull) was procured from thirty Murrah buffalo bulls. Additionally, fresh semen of same ejaculate of each bull was also separated for seminal plasma for ASA analysis. Blood samples of all bulls were collected in non-heparinized vials and serum was harvested from them. The ASA, IgA- and IgG-bound spermatozoa were analyzed in blood serum and seminal plasma by immuno-peroxidase assay (IPA) and immunobead-binding assay (IBA). On the basis of per cent ASA, IgA- and IgG-type, all bulls were divided into 2 groups viz. group 1 (< 40% ASA, IgA and IgG in serum; < 20% ASA, IgA and IgG in seminal plasma) and group 2 (> 40% ASA, IgA and IgG in serum; > 20% ASA, IgA and IgG in seminal plasma) for further comparisons. The frozen-thawed semen was also evaluated for percent motility (total and progressive), concentration, viability, abnormality, HOST, acrosome integrity, acrosome reaction, CMPT and first FSCR. The percentage of ASA (37.1±3.8 vs 22.3±1.5), IgA- (44.2±3.1 vs 21.6±2.7) and IgG-bound spermatozoa (35.5±3.0 vs 19.7±4.6) were significantly higher in serum than in seminal plasma. In blood serum, sperm motility, acrosome reaction, CMPT and FSCR were significantly higher in bulls with < 40% ASA as compared to their counterparts. In seminal plasma, bulls with < 20% ASA exhibited significantly higher sperm concentration as compared to their contemporary mates. Sperm concentration (982.2±50.4 vs 874.9±36.3%) in blood serum and acrosome reaction (56.6±2.7 vs 49.9±2.3%) in seminal plasma were the only parameters that were significantly higher in bulls with < 40% and < 20% IgA, respectively than in their counterparts. For IgG-type, sperm concentration and acrosome reaction were significantly higher in bulls with < 40% than in those with > 40% IgG in blood serum. In seminal plasma, acrosome reaction and FSCR were significantly higher in bulls with < 20% IgG than in their contemporary mates. In conclusion, detection of surface-bound ASA was associated with changes in quality and fertility of buffalo bull semen.